2020
DOI: 10.21873/anticanres.14336
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Abnormal Findings on Ring-type Dedicated Breast PET for the Detection of Breast Cancer

Abstract: Aim: To investigate the usefulness of classification of ring-type dedicated breast positron-emission tomography (dbPET) findings in detection of breast cancer. Patients and Methods: A total of 709 patients with breast cancer underwent dbPET before treatment. Each finding was morphologically categorized as a focus (uptake size ≤5 mm), mass (>5 mm), or non-mass (multiple uptakes not belonging to a three-dimensional mass or without distinct mass features). Non-mass uptakes were additionally classified as linear, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Satoh et al found that mass uptake was significantly associated with malignancy compared to focus in 40 unexpected uptake lesions in 35 patients [ 13 ]. Sasada et al showed that mass and focal/segmental non-mass lesions were significantly associated with breast cancer among 910 abnormal findings in 709 patients with breast cancer [ 14 ]. Masumoto et al reported that heterogeneity in tumor uptake was associated with higher nuclear grade and higher Ki67 in breast cancers [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satoh et al found that mass uptake was significantly associated with malignancy compared to focus in 40 unexpected uptake lesions in 35 patients [ 13 ]. Sasada et al showed that mass and focal/segmental non-mass lesions were significantly associated with breast cancer among 910 abnormal findings in 709 patients with breast cancer [ 14 ]. Masumoto et al reported that heterogeneity in tumor uptake was associated with higher nuclear grade and higher Ki67 in breast cancers [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Narayanan et al first reported the value of feature analysis of breast uptake using PEM with 18 F-fluorodeoxyglucose ( 18 F-FDG), and demonstrated morphological uptake features of additional lesions in patients with breast cancer were significant predictors of malignancy [ 12 ]. In recent years, there have been several reports that suggest the usefulness of breast lesion morphological assessment using a ring-type dbPET with 18 F-FDG [ 13 , 14 , 15 , 16 ]. However, to establish and facilitate a comprehensive approach of breast cancer diagnosis using dbPET, there is now a critical need to standardize reporting and descriptors of uptake features.…”
Section: Introductionmentioning
confidence: 99%